2011
DOI: 10.1017/s000708741100032x
|View full text |Cite
|
Sign up to set email alerts
|

Charles Darwin's use of theology in the Origin of Species

Abstract: This essay examines Darwin's positiva (or positive) use of theology in the first edition of the Origin of Species in three steps. First, the essay analyses the Origin's theological language about God's accessibility, honesty, methods of creating, relationship to natural laws and lack of responsibility for natural suffering; the essay contends that Darwin utilized positiva theology in order to help justify (and inform) descent with modification and to attack special creation. Second, the essay offers critical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, this idea is not in conflict with views claiming that the use of theology played an epistemic role in the OS's case for evolution, and against special creation(Dilley 2012). Excellent analyses on Darwin's use of theology can also be found inGillespie 1979;Ospovat 1980;Brooke 1985Brooke , 2008Kohn 1989;Depew 2008, to mention a few.…”
mentioning
confidence: 99%
“…Nevertheless, this idea is not in conflict with views claiming that the use of theology played an epistemic role in the OS's case for evolution, and against special creation(Dilley 2012). Excellent analyses on Darwin's use of theology can also be found inGillespie 1979;Ospovat 1980;Brooke 1985Brooke , 2008Kohn 1989;Depew 2008, to mention a few.…”
mentioning
confidence: 99%
“…As I will argue below, however, these rivals do not necessarily hold the same view of God as 'special creation' does. With respect to these rivals, then, I argue that Gould uses what we may call "positiva theology" (Dilley 2012). 8 This theology tries to establish evolution and refute design rivals by drawing upon theology that is, in some sense, foreign to these rivals.…”
Section: Definitionsmentioning
confidence: 99%
“…270, 297, 332, 341, 351, 354, 356, 362, 364, 369, 371, 375, 388-89, 390-96;de Beer 1964, pp. 46-48, 55, elliptically;Dilley 2012Dilley , 2013Dilley , 2017Diogo and Molnar 2016;Dobzhansky 1973;Eldredge 2000, pp. 99-100, 144-46;Forterre and Gadelle 2009;Futuyma 1995, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have suggested more radical interpretations; see, for instance, Southgate () and Dilley ().…”
mentioning
confidence: 99%